2023
DOI: 10.3389/fpls.2023.1135312
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral adaptation of sympatric rodents to early germination of oak acorns: radicle pruning and embryo excision

Abstract: The seed germination schedule is a key factor affecting the food-hoarding behavior of animals and the seedling regeneration of plants. However, little is known about the behavioral adaptation of rodents to the rapid germination of acorns. In this study, we provided Quercus variabilis acorns to several rodent species to investigate how food-hoarding animals respond to seed germination. We found that only Apodemus peninsulae adopted embryo excision behavior to counteract seed germination, which is the first repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Previous studies revealed that many species (e.g. Apodemus sylvaticus , Niviventer confucianus and Dremomys rufigenis ) showed behaviour of cutting radicle or removing embryos of seeds (Xiao & Zhang, 2012; Cao et al ., 2022; Zhang et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that many species (e.g. Apodemus sylvaticus , Niviventer confucianus and Dremomys rufigenis ) showed behaviour of cutting radicle or removing embryos of seeds (Xiao & Zhang, 2012; Cao et al ., 2022; Zhang et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%